1992
DOI: 10.1007/bf00031916
|View full text |Cite
|
Sign up to set email alerts
|

Structure and dynamics of Japanese beech (Fagus japonica Maxim.) stools and sprouts in the regeneration of the natural forests

Abstract: Structure and spatial distribution of stools and root-collar sprouts of Japanese beech (Fagus japonica) were studied to clarify the regeneration processes of the stool and the population, and the ecological importance of this stool formation in five quadrats of the natural forests with different forest floor vegetation on the Pacific side of Japan. F. japonica dominates in the canopy of each quadrat. Most of sprouts formed a circle around the root-collar and lowest parts of the parent stems of the stool wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 12 publications
1
47
0
Order By: Relevance
“…Main medium sized tree and shrub species were Acer Shirasawanum, A. distylum and Fraxinus lanuginosa in Okukinu and Prunus grayana, Meliosma myriantha and Carpinus cordata in Takahara, respectively. The undergrowth was dominated by 0.6 m tall dwarf bamboo, Sasa nipponica, which covered 43% of the area in Okukinu and 88% in Takahara (Ohkubo 1992).…”
Section: Study Sites and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Main medium sized tree and shrub species were Acer Shirasawanum, A. distylum and Fraxinus lanuginosa in Okukinu and Prunus grayana, Meliosma myriantha and Carpinus cordata in Takahara, respectively. The undergrowth was dominated by 0.6 m tall dwarf bamboo, Sasa nipponica, which covered 43% of the area in Okukinu and 88% in Takahara (Ohkubo 1992).…”
Section: Study Sites and Methodsmentioning
confidence: 99%
“…grosseserrata and some Acer species. Throughout its geographic distribution range, E japonica stems naturally form vigorous sprouts from the root-collar (Tohyama 1965;Ohkubo et al 1988;Peters & Ohkubo 1990;Ohkubo 1992). The sprouts are connected with each other at their epigeal parts and form a permanent base of a individual tree (here we call 'stool').…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sprouts under a canopy of Fagus japonica Maxim. continue to grow after the death of the main stem (Peter and Ohkubo, 1990), and the stand expands and disconnects (Ohkubo, 1992). Ohkubo et al (1996) suggested that these sprouts play a role in 'sprout banks', analogous to seedling banks (Bellingham et al, 1994).…”
Section: Sprout Occurrence and Growth In Relation To Light Conditionsmentioning
confidence: 99%
“…On the other hand, in the absence of human activities, tree species that produce many sprouts are mostly found in areas that experience disturbances, such as heavy snowfall (Okitsu, 1991;Tanimoto, 1993), coastal winds (Ito, 1993;Ito and Gyokusen, 1996), and steep slopes (Sakai et al, 1995), where conditions are generally too severe for seedlings to regenerate. Therefore, sprouting likely compensates for sparse seedling regeneration (Hara, 1987;Ohkubo, 1992;Kruger et al, 1997). Even in stable forests, sprouting plays an important role in the maintenance of forest vegetation by repairing the forest canopy after gap formation (Koop, 1987;Ohkubo et al, 1988Ohkubo et al, , 1996Peter and Ohkubo, 1990).…”
Section: Introductionmentioning
confidence: 99%